Smiertelne zauroczenie - Collins, Jackie; Dobrzanska-Gadowska, Anna. (Warszawa : Libros, 2001)
Polish translation of "Lethal Seduction". A romantic suspense novel about women journalists involved with the Mafia.
Translation of: Lethal seduction.
Keywords: Women journalists -- Fiction; Mafia -- Fiction; New York (N.Y.) -- Fiction; Las Vegas (Nev.) -- Fiction